Correction to: 2021 Taxonomic update of phylum Negarnaviricota (Riboviria: Orthornavirae), including the large orders Bunyavirales and Mononegavirales - Jens H. Kuhn; Scott Adkins; Bernard R. Agwanda; Rim Al Kubrusli; Sergey V. Alkhovsky; Gaya K. Amarasinghe; Tatjana Avšič-Županc; María A. Ayllón; Justin Bahl; Anne Balkema-Buschmann; Matthew J. Ballinger; Christopher F. Basler; et al. (Archives of Virology, 2021)

2021 Taxonomic update of phylum Negarnaviricota (Riboviria: Orthornavirae), including the large orders Bunyavirales and Mononegavirales - Jens H. Kuhn; Scott Adkins; Bernard R. Agwanda; Rim Al Kubrusli; Sergey V. Alkhovsky; Gaya K. Amarasinghe; Tatjana Avšič-Županc; María A. Ayllón; Justin Bahl; Anne Balkema-Buschmann; Matthew J. Ballinger; Christopher F. Basler; et al. (Archives of Virology, 2021)

Tracing the origins of recent Queensland fruit fly incursions into South Australia, Tasmania and New Zealand - Ángel-David Popa-Báez; Siu Fai Lee; Heng Lin Yeap; Guy Westmore; Peter Crisp; Dongmei Li; Renee Catullo; Emilie C. Cameron; Owain R. Edwards; Phillip W. Taylor; John G. Oakeshott (Biological Invasions, 2021)

Environmental Heterogeneity Throughout the Clarion-Clipperton Zone and the Potential Representativity of the APEI Network - Travis W. Washburn; Daniel O. B. Jones; Chih-Lin Wei; Craig R. Smith (Frontiers in Marine Science, 2021)
Environmental variables such as food supply, nodule abundance, sediment characteristics, and water chemistry may influence abyssal seafloor communities and ecosystem functions at scales from meters to thousands of kilometers. Thus, knowledge of environmental variables is necessary to understand drivers of organismal distributions and community structure, and for selection of proxies for regional variations in community structure, biodiversity, and ecosystem functions. In October 2019, the Deep CCZ Biodiversity Synthesis Workshop was conducted to (i) compile recent seafloor ecosystem data from the Clarion-Clipperton Zone (CCZ), (ii) synthesize patterns of seafloor biodiversity, ecosystem functions, and potential environmental drivers across the CCZ, and (iii) assess the representativity of no-mining areas (Areas of Particular Environmental Interest, APEIs) for subregions and areas in the CCZ targeted for polymetallic nodule mining. Here we provide a compilation and summary of water column and seafloor environmental data throughout the CCZ used in the Synthesis Workshop and in many of the papers in this special volume. Bottom-water variables were relatively homogenous throughout the region while nodule abundance, sediment characteristics, seafloor topography, and particulate organic carbon flux varied across CCZ subregions and between some individual subregions and their corresponding APEIs. This suggests that additional APEIs may be needed to protect the full range of habitats and biodiversity within the CCZ.

The stratigraphic significance of early Cambrian (Series 2, Stage 4) trilobites from the Smith Bay Shale near Freestone Creek, Kangaroo Island - J. B. Jago; C. J. Bentley; J. R. Paterson; J. D. Holmes; T. R. Lin; X. W. Sun (Australian Journal of Earth Sciences, 2021)